Kajian Keberkesanan Penyenggaraan Fasiliti dalam Pengurusan Sisa Pepejal di Kawasan Program Perumahan Rakyat(PPR) Seri Pantai, Kuala Lumpur - Shamsudin, Nurul Syafiqah; Mohamed, Sulzakimin; Omar, Roshartini; Sarpin, Norliana; Shafii, Haryati (Research in Management of Technology and Business, 2021)
In Malaysia, public houses such as the People's Housing Program (PPR) require good solid waste facility management in order to provide comfort and safety to the residents of the area. Facility management is an important element that supports the building management and maintenance system. It is also important to ensure that the building environment is always in a tidy and maintained condition, especially buildings that have a high population density and public concentration. However, not all solid waste management emphasizes the maintenance aspect in accordance with the specified management and maintenance system specifications. Imperfect solid waste maintenance can have a negative impact on residents who expect good service delivery and can overcome the problem of unsystematic waste disposal at PPR Seri Pantai. Therefore, a study was conducted to identify the problem of solid waste facility maintenance occurs and find a suitable method to solve it based on the objectives of the study. This study was conducted at PPR Seri Pantai conducted in a qualitative manner by holding an interview session with the City of Kuala Lumpur (DBKL) and observations were also conducted to obtain more information and depth. Therefore, the parties involved must play a role to ensure that solid waste management in the People's Housing Project can be managed appropriately. Through the results of this study, it is hoped to provide useful information to the management of facilities in all people's housing programs (PPR) in overcoming the problem of maintenance of solid waste facilities.